Braneworld Black Hole Gravitational Lensing - 梁钧 (Communications in theoretical physics, 2017)
A class of braneworld black holes, which I called as Bronnikov–Melnikov–Dehen（BMD） black holes,are studied as gravitational lenses. I obtain the deflection angle in the strong deflection limit, and further calculate the angular positions and magnifications of relativistic images as well as the time delay between different relativistic images. I also compare the results with those obtained for Schwarzschild and two braneworld black holes, i.e., the tidal Reissner-Nordstr¨om（R-N） and the Casadio–Fabbri–Mazzacurati（CFM） black holes.